A new species of Leptoderma Vaillant, 1886 (Osmeriformes: Alepocephalidae) from the Pacific coast of Central America - Angulo, Arturo; Baldwin, Carole C.; Robertson, D. Ross (Zootaxa, 2016)
A new species of Leptoderma Vaillant, 1886 is described from a single specimen trawled at 1368–1406 m depth off El Salvador, Central America, tropical eastern Pacific. Leptoderma ospesca n. sp. can be readily distinguished from its congeners by the following combination of characters: dermal papillae absent along the lateral line, pectoral-fin rays 6, pelvic-fin rays 5, pre-dorsal length 54.9% of SL, both dorsal and anal fins separated from the caudal fin, dorsal- and anal-fin rays long, procurrent caudal-fin rays numerous and extending far forward on caudal peduncle, caudal-fin rays 16, and total pre-ural vertebrae 60. A key to the species of the genus is presented.